Revisión Documental en Iberoamérica entre los años 2012- 2021 Sobre las Distorsiones Cognitivas en Abusadores Sexuales de Niños (2021)
The present research is a descriptive bibliographic review of academic and scientific sources that describe the cognitive distortions in a sexual abuser of minors, found in Latin America in the years 2012-2021. cognitive characteristics of the sexual abusers of children and adolescents, the most relevant characteristics found in the aforementioned studies are described there. Under the qualitative theoretical approach, fifty sources were compiled that include articles, books and reports from public and private organizations that have developed studies on the subject.